2016
DOI: 10.3402/ejpt.v7.30713
|View full text |Cite
|
Sign up to set email alerts
|

Early maladaptive schemas in adult survivors of interpersonal trauma: foundations for a cognitive theory of psychopathology

Abstract: BackgroundAlthough the association between psychological trauma and early maladaptive schemas (EMS) is well established in the literature, no study to date has examined the relationship of EMS to PTSD and psychopathologies beyond depression and anxiety in a sample of adult survivors of interpersonal trauma. This information may be useful in helping our understanding on how to best treat interpersonal trauma.ObjectiveWe set out to investigate the association between EMS and common forms of psychopathology in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Results showed significantly lower emotional SE in adult IM survivors compared to the norm sample [ 38 ]. Although the observed effect was small, this finding is consistent with previous research reporting low emotional SE in other clinical samples [ 51 , 52 ]. Thus, we assume that experiencing IM negatively affects self-related associations and emotions, and supports our first hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…Results showed significantly lower emotional SE in adult IM survivors compared to the norm sample [ 38 ]. Although the observed effect was small, this finding is consistent with previous research reporting low emotional SE in other clinical samples [ 51 , 52 ]. Thus, we assume that experiencing IM negatively affects self-related associations and emotions, and supports our first hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…The authors proposed a minimum number of participants to achieve 0.8 power depending on the magnitude of the estimated effect sizes for the 'a' and 'b' mediation pathways. Previous research (Foa, Ehlers, Clark, Tolin, & Orsillo, 1999;Karatzias et al, 2016;Wright, Crawford, & Del Castillo, 2009) has indicated large effect sizes for the 'a' and 'b' pathways. Based on these findings, a sample size of 36 was deemed appropriate.…”
Section: Resultsmentioning
confidence: 93%
“…Research examining the relative contribution of schema domains in PTSD severity has indicated a stronger association between schemas within the Disconnection and Impaired Autonomy domains and PTSD (Harding, Burns, & Jackson, 2012;Karatzias, Jowett, Begley, & Deas, 2016;Price, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations